2011
DOI: 10.1029/2010pa002065
|View full text |Cite
|
Sign up to set email alerts
|

The Benguela upwelling related to the Miocene cooling events and the development of the Antarctic Circumpolar Current: Evidence from calcareous dinoflagellate cysts

Abstract: Sediment samples from ODP Site 1085 were investigated in order to obtain more information on the initiation and development of the Benguela upwelling system during the middle and upper Miocene. In particular, our intent was to establish the causes of the upwelling as well as the response of the upwelling regime to the development of the Antarctic Circumpolar Current. Based on changes in the calcareous dinoflagellate cyst association, we found an initial increase of the dinoflagellate cyst productivity, probabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 94 publications
2
32
0
Order By: Relevance
“…This developed as a tear in the South American plate, on which the Northeast Georgia Rise is located, as the South Sandwich subduction zone retreated eastward (Barker, 1995;Smalley et al, 2007;Govers and Wortel, 2005). Interestingly, polar calcareous dinofl agellate cyst species fi rst appear in the sedimentary record off southwestern Africa at 11.1 Ma (Heinrich et al, 2011), also supporting a late Miocene ACC onset.…”
Section: Tectonic and Paleoenvironmental Implicationsmentioning
confidence: 88%
“…This developed as a tear in the South American plate, on which the Northeast Georgia Rise is located, as the South Sandwich subduction zone retreated eastward (Barker, 1995;Smalley et al, 2007;Govers and Wortel, 2005). Interestingly, polar calcareous dinofl agellate cyst species fi rst appear in the sedimentary record off southwestern Africa at 11.1 Ma (Heinrich et al, 2011), also supporting a late Miocene ACC onset.…”
Section: Tectonic and Paleoenvironmental Implicationsmentioning
confidence: 88%
“…14 Ma. Alternatively, the mode and tempo of aridification (van Zinderen Bakker, ; Heinrich et al ., ) could imply that the ancestor of the subtribe was pre‐adapted to arid environments. As the number of large‐scale biogeographical studies of Namib Desert plants is few, it remains unknown if this is a unique/rare example or part of a more common pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Zonneveld et al (1997) reported that the total abundance of cysts in oxidised sediments was only about 10% of that observed in unoxidised sediments, a difference explained by a selective preservation of cyst species due to different oxygen conditions, rather than to the differential settling of grains. Moreover, the solubility of calcium carbonate increases with decreasing temperature (Vink et al 1999, Heinrich et al 2011, contributing to partial to complete dissolution of the calcareous components of the cyst wall.…”
Section: Distributionmentioning
confidence: 99%